Reading associations in England and Scotland, c. 1760-1830 - Lindsay, C (2016)
This thesis examines provincial literary culture in the late eighteenth and early nineteenth century, through the printed and manuscript records of reading associations, the diaries of their members, and a range of other print materials. These book clubs and subscription libraries have often been considered to be polite and sociable institutions, part of the cultural repertoire of a new urban, consumer society. However, this thesis reconsiders reading associations’ values and effects through a study of the reading materials they provided, and the reading habits they encouraged; the intellectual and social values which they embodied; and their role in the performance of gender, local and national identities. It questions what politeness meant to associational members, arguing for the importance of morality and order in associational conceptions of propriety, and downplaying their pursuit of structured sociability. This thesis examines how provincial individuals conceived of their relationship to the reading public, arguing that associations provided a tangible link to this abstract national community, whilst also having implications for the 'public' life of localities and families. The thesis also considers how these institutions interacted with enlightenment thought, suggesting that both the associations' reading matter and their philosophies of corporate improvement enabled 'ordinary' men and women to participate in the Enlightenment. It assesses English and Scottish associations, which are usually subjected to separate treatment, arguing that they constituted a shared mechanism of British literary culture in this period. More than simply a 'polite' performance, reading, through associations, was fundamentally linked to status, to citizenship, and to cultural participation.